Organizational commitment and job satisfaction of staff nurses as determinants of nursing service quality in hospitals: a literature review - Misrayanti, Misrayanti; Anggeria, Elis; Mahaputera Maritua Hutapea, Dwight (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Background: The quality of nursing services is a key indicator of hospital service quality. Job satisfaction and organizational commitment among staff nurses have been reported to play a major role in shaping performance, work behavior, and the quality of nursing care; however, existing evidence remains fragmented and has not been systematically synthesized. Objective: To conduct a systematic review of the influence of nurses’ job satisfaction and organizational commitment on the quality of nursing services in hospitals. Methods: This systematic review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed using Google Scholar, PubMed, ScienceDirect, and other indexed journal databases. Inclusion criteria covered quantitative, qualitative, and literature review studies involving hospital nurses and examining job satisfaction, organizational commitment, and nursing performance or service quality. Risk of bias was assessed using simplified versions of the JBI and CASP tools. Data were synthesized narratively. Results: A total of 15 articles met the inclusion criteria. Most studies employed cross-sectional designs. The findings consistently showed that job satisfaction was positively associated with organizational commitment, which in turn contributed to improved performance, Organizational Citizenship Behavior (OCB), and nursing service quality. Organizational factors such as organizational justice, internal service quality, managerial support, and employee well-being played significant roles. Conclusion: Job satisfaction and organizational commitment are key determinants of nursing service quality. Efforts to improve nurses’ work environments have the potential to enhance overall hospital service quality.